The Liars Society - Gerber, Alyson (New York, NY : Scholastic Inc., 2024)
"Weatherby is a fish out of water. When she lands a scholarship to the prestigious Boston School, she's excited to be in the same world as her dad...But Weatherby has a secret she'll risk everything to protect, one that could destroy her new life. Every member of Jack's wealthy and privileged family has made their mark at the Boston School. Everyone, that is, except for Jack, who is entirely mediocre...But Jack has a secret of his own...one with the power to ruin everything.When the money for their schooltrip to a private island...is stolen, Jack and Weatherby are invited to play a high-stakes game and solve the mystery of the missing money"--.
new kids book 2024 winter.
Keywords: Private schools -- Juvenile fiction; Rich people -- Juvenile fiction; Secrecy -- Juvenile fiction; Theft -- Juvenile fiction; Mystery and detective stories; Sailing; Social classes; Preparatory schools; Boston (Mass.); Massachusetts; Novels; Detective and mystery fiction; Detective fiction; Mystery fiction